Evaluation of the stress concentration of different incisal ridge preparations of porcelain veneers (Finite element analysis) - Al-Huwaizi, Abbas F (Journal of Baghdad College of Dentistry, 2013)
Background: Porcelain veneers are under a great deal of stress which may lead to clinical failure as fracture or dettachment. This study examined whether different finishing lines and lingual shoulder preparations in the incisal area of the maxillary central incisor affect the bond of the porcelain veneers. Materials and methods: A two- dimensional finite element model was made. Location and magnitude of maximum Von Mises stresses were calculated in porcelain veneer. Six types of preparations were drawn as:incisal overlap of 0.5mm, 1mm and 1.5mm depth and lingual shoulder, and incisal overlap of 0.5mm, 1mm and 1.5mm depth without shoulder preparation. Results: Stress formation is maximum in the incisal edge region. All the lingual shoulder preparations presented better stress distribution than the non shoulder preparations Conclusion: Stress is distributed more evenly when the tested preparation possesses a good thickness of porcelain and the more the surface area with incisal overlap the less possibility of bond failure.